The role of information and communications technology in achieving innovation in organizations: Case study of the Djelfa Mills Company - Bendenidina, Saida; Benahmed, Fatima Zahra; Benahmed, Nadia (International journal of economic perspectives, 2025)
This study highlights the role of information and communication technology in achieving Innovation in organizations. To achieve the study's objectives, we relied on a questionnaire, which was designed and directed to a group of employees at the Djelfa Mills Company. Fifty questionnaires were retrieved, all of which were valid for analysis, the validity and reliability of the study tool were verified. This study concluded that there is a statistically significant effect of each of (availability of information and communication technology means, use of information and communication technology means, and information system) in combination on achieving Innovation in the Djelfa Mills Company.